The Effect of Educational Facilities and Infrastructure Management and Teacher Professionalism on Educational Quality in Public Elementary Schools in Tungkal Ilir District, Banyuasin Regency - Indah Permatasari; Nuril Furkan; Nurlina (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aimed to analyze the effects of educational facilities and infrastructure management and teacher professionalism on educational quality in public elementary schools in Tungkal Ilir District, Banyuasin Regency. A quantitative ex post facto design was employed. The population comprised 193 teachers, while 65 teachers from A- and B-accredited schools were selected through purposive sampling. Data were collected using Likert-scale questionnaires and documentation. The instruments demonstrated high internal consistency, with Cronbach's alpha coefficients of 0.908 for facilities and infrastructure management, 0.913 for teacher professionalism, and 0.902 for educational quality. Data were analyzed using descriptive statistics, prerequisite tests, simple linear regression, and multiple linear regression with SPSS version 26. Facilities and infrastructure management had a positive and significant effect on educational quality (B = 0.165; t = 2.854; p = 0.006; R² = 11.4%). Teacher professionalism also had a positive and significant effect (B = 0.232; t = 3.403; p = 0.001; R² = 15.5%). Simultaneously, both predictors significantly affected educational quality (F = 8.313; p = 0.001; R² = 21.1%), with the equation Y = 2.836 + 0.120X1 + 0.191X2. The findings show that integrated improvement of school-facility management and teacher professionalism is necessary to strengthen educational quality.